Establishing a risk stratification model to identify clinically high-risk N0 breast cancer who could benefit from regional nodal irradiation: a single institute analysis - Cao, Lu; Ou, Dan; Li, Shuyan; Xu, Cheng; Cai, Rong; Xu, Haoping (Frontiers in Oncology, 2024)
BackgroundThe purpose of this real-world study was to investigate the risk factors for developing recurrence among patients with pathological T1-3N0 breast cancer (BC) treated with breast-conserving surgery (BCS) followed by whole breast irradiation alone (WBI) and identify those clinically high-risk BCs who could benefit from regional nodal irradiation (RNI).Materials and methodsFemale BC patients treated at Shanghai Ruijin hospital from 2009 to 2016 were retrospectively reviewed. The disease-free survival (DFS), breast cancer specific survival (BCSS) and overall survival (OS) were estimated by the Kaplan-Meier method, and survival differences were compared with the log-rank test. Univariate and multivariate analysis was performed using Cox proportional hazards regression analysis. An external validation was conducted by using SEER database.ResultsA total of 622 BC patients treated with BCS+WBI alone were included. With a median follow-up of 82 months, the 7-year OS, BCSS and DFS for the entire cohort was 97%, 99% and 91%, respectively. Multivariable Cox analysis indicated that tumor size (p=0.006), tumor location (p=0.033), lymphovascular invasion (LVI) status (p=0.0028) and Ki-67 index (p=0.051) were independent risk factors for DFS. A scoring system was developed using these four factors and the 7-year DFS and OS were 97% and 96% for patients with 0-1 risk factors, 95% and 82% for patients with ≥2 risk factors (p<0.0001 for DFS, and p=0.0063 for OS). Based on tumor size and tumor location, an external validation by demonstrated that the 7-year OS was 90% and 88% for patients with 0-1 risk factor, which was significantly better than those defined as high-risk BC patients (82%, p<0.0001).ConclusionBy using our institute database, we establish a risk stratification system for identifying sub-group of pN0 BC patients, who are at high risk for developing recurrence. The results of our study support tailored RT decision-making according to individual risks, which needed to be confirmed in further studies.